2002
DOI: 10.1523/jneurosci.22-09-03683.2002
|View full text |Cite
|
Sign up to set email alerts
|

Internally Simulated Movement Sensations during Motor Imagery Activate Cortical Motor Areas and the Cerebellum

Abstract: It has been proposed that motor imagery contains an element of sensory experiences (kinesthetic sensations), which is a substitute for the sensory feedback that would normally arise from the overt action. No evidence has been provided about whether kinesthetic sensation is centrally simulated during motor imagery. We psychophysically tested whether motor imagery of palmar flexion or dorsiflexion of the right wrist would influence the sensation of illusory palmar flexion elicited by tendon vibration. We also te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
163
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(183 citation statements)
references
References 69 publications
(117 reference statements)
20
163
0
Order By: Relevance
“…In visuomotor tasks, movement planning then would equal the process of analyzing the difference between the current sensory state and the prospective sensory state, which is predicted to result from the currently imagined movement in the future, once it is executed (Salinas, 2004;Shadmehr and Wise, 2005). This view is consistent with our data and previous studies, which showed activation of PPC during motor imagery (Decety et al, 1994;Stephan et al, 1995;Sirigu et al, 1996;Gerardin et al, 2000;Naito et al, 2002), and the fact that parietal electrical stimulation can trigger subjective movement intentions without actual movements being performed (Desmurget et al, 2009). …”
Section: Frontoparietal Projections For Prospective Forward Model Estsupporting
confidence: 94%
“…In visuomotor tasks, movement planning then would equal the process of analyzing the difference between the current sensory state and the prospective sensory state, which is predicted to result from the currently imagined movement in the future, once it is executed (Salinas, 2004;Shadmehr and Wise, 2005). This view is consistent with our data and previous studies, which showed activation of PPC during motor imagery (Decety et al, 1994;Stephan et al, 1995;Sirigu et al, 1996;Gerardin et al, 2000;Naito et al, 2002), and the fact that parietal electrical stimulation can trigger subjective movement intentions without actual movements being performed (Desmurget et al, 2009). …”
Section: Frontoparietal Projections For Prospective Forward Model Estsupporting
confidence: 94%
“…From the flexor muscle (the FCU), we found no robust EMG activity during the illusions. These EMG results confirmed those in our previous studies (Naito et al, 2002a(Naito et al, ,b, 2005.…”
Section: Psychophysical Evaluationsupporting
confidence: 93%
“…a protoractor [see methods in the study by Naito et al (2002a)]. The subjects were also requested to rate the vividness of illusions on an analog scale from 1 to 10.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, brain's neuroimaging exploration provided evidences that similar neural structures, including the parietal and prefrontal cortices, the supplementary motor area, the premotor and primary motor cortices, the basal ganglia, the cerebellum, and for some motor tasks the spinal cord, are engaged during both movement execution and internal simulation (for a review see [11,15,21]). Specifically, this overlap has been reported for hand movements [25,31], finger-to-thumb movements [38], toe and tongue movements [14] as well as during walking [29]. It has also been shown that muscular force is enhanced by an 'imagined' training [39,51] and that autonomic activation is increased, compared to rest, when subjects imagine motor actions with large physical effort [8,9,33].…”
Section: Introductionmentioning
confidence: 84%